2010
DOI: 10.1088/0004-637x/710/2/1724
|View full text |Cite
|
Sign up to set email alerts
|

HAT-P-11b: A SUPER-NEPTUNE PLANET TRANSITING A BRIGHT K STAR IN THEKEPLERFIELD

Abstract: We report on the discovery of HAT-P-11b, the smallest radius transiting extrasolar planet (TEP) discovered from the ground, and the first hot Neptune discovered to date by transit searches. HAT-P-11b orbits the bright (V=9.587) and metal rich ([Fe/H] = +0.31 ± 0.05) K4 dwarf star GSC 03561-02092 with P = 4.8878162 ± 0.0000071 days and produces a transit signal with depth of 4.2 mmag; the shallowest found by transit searches that is due to a confirmed planet. We present a global analysis of the available photom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
500
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(517 citation statements)
references
References 98 publications
16
500
1
Order By: Relevance
“…Our finding that the planet is about 4.23 times bigger than the Earth in radius agrees closely with the NEA value of 4.68 R ⊕ , and in apparent exact agreement with that of Bakos et al (2010). Bakos et al (2009Bakos et al ( , 2010 found an eccentricity of 0.198 to the planetary orbit, having a periastron longitude of ∼355 • with a formal error of about 15 • . In other words, the major axis of the elliptical orbit is not far from the plane of the sky, the planet exiting from the transit more quickly than its entrance.…”
Section: Individual Systemssupporting
confidence: 89%
“…Our finding that the planet is about 4.23 times bigger than the Earth in radius agrees closely with the NEA value of 4.68 R ⊕ , and in apparent exact agreement with that of Bakos et al (2010). Bakos et al (2009Bakos et al ( , 2010 found an eccentricity of 0.198 to the planetary orbit, having a periastron longitude of ∼355 • with a formal error of about 15 • . In other words, the major axis of the elliptical orbit is not far from the plane of the sky, the planet exiting from the transit more quickly than its entrance.…”
Section: Individual Systemssupporting
confidence: 89%
“…Dedicated surveys have proven to be more efficient for transit detections. Ground-based programs allow Jupiter-size planets to be detected with improving accuracies which now point toward planets with smaller radii (Bakos et al 2010), whereas space-based programs allow planets with even smaller radii to be detected (Léger et al 2009;Queloz et al 2009), as well as planets with longer periods (Moutou et al 2009b). If accepted, the ESA-proposed space mission PLATO (Catala et al 2009) could permit the detection of this kind of transiting planets in front of brighter stars.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noticing that most of the baseline parameters are not jump parameters in the MCMC, they are deduced by least-square minimization from the residuals at each step of the chains, thanks to their linear nature in the baseline functions (Bakos et al 2009;). …”
Section: Methods and Modelsmentioning
confidence: 99%